Self-medication in Brazil during the pandemic of COVID-19 and the role of the pharmaceutical professional, a systematic review (Research, Society and Development, 2021)
Although self-medication is a common practice, it can lead to several health problems, such as masking diseases, causing drug interactions, bacterial resistance and intoxication. During the COVID-19 pandemic many news articles were spread encouraging the use of drugs for the prevention and treatment of SARS-CoV-2, such as chloroquine, hydroxychloroquine, nitazoxanide, ivermectin, etc. However, there is no scientific proof of their efficacy for this purpose. The objective of the present study was to systematically review the existing literature on self-medication and relate it to the COVID-19 pandemic. A literature review search was performed and a total of 27 scientific articles were summarized and discussed. Self-medication as a result of panic, bad information, and the culture that Brazilians have of self-diagnosing have collaborated to the increase of these practices. Misinformation in the social networks about pharmacological treatments favored the shortage of pharmacies and drugstores, harming even hospital care. Drugs advertised as prophylactic and curative for the new coronavirus proved to be ineffective in vivo clinical trials applied mostly in hospitalized patients with COVID-19, except for remdesivir and dexamethasone, which contributed significantly in the treatment of moderate to severe cases. Pharmaceutical professionals were important in raising public awareness about the adverse effects of drugs, fighting fake news, and producing vaccines. It was also possible to observe the lack of resources that Brazilian universities have to generate science, making financial support necessary to enable research into new drugs and vaccine manufacturing.